Effect of Ghrelin on Pain Threshold in Mice - Kutlu, Selim; Ozcan, Mete; Canpolat, Sinan; Sandal, Süleyman; Aydın, Mehmet; Kelestimur, Haluk (Fırat University, 2005)
Objectives: Ghrelin, a novel growth hormone-releasing peptide, was isolated from the rat stomach as an endogenous ligand for the growth hormone secretagogues receptor. The present study was planned to determine whether ghrelin affects pain threshold in mice. Materials and Methods: Adult male BALB/C mice weighing 25–30g were used in this study. The hot plate test was conducted by placing the mouse on a metal surface maintained at 50±0.1ºC by using hot plate analgesia meter. The latency to jumping or licking a hind paw was recorded as nociceptive threshold. Animals were allowed to acclimate to the hot plate for a period of 1 week prior to the experiment. Different doses of ghrelin were intraperitoneally administered to the animals after control latencies. Control group received saline alone. Hot plate test were performed in all animals individually in 30 th, 60 th, 90 th and 120 th minutes after injection. Pain threshold values were determined and analyzed by Mann-Whitney U Test and Wilkoxon Sign Ranks Test. Results: Ghrelin didn't affect pain threshold throughout the experiment in 0.3pmol and 1pmol doses compared to control values. There were significant decreases in pain threshold when it is given in a dose of 3pmol in 30 th and 60 th minutes (p

Amaç: Yeni bir büyüme hormonu salgılatıcı peptit olan grelin, büyüme hormonu salgılatıcı reseptörlerin endojen bir ligandı olarak sıçan midesinden izole edilmiştir. Bu çalışma, grelinin farelerde ağrı eşiği üzerindeki olası etkilerini belirlemek amacıyla planlanmıştır. Gereç ve Yöntem: Çalışmada 25-30 gram ağırlığında yetişkin erkek BALB/C fareler kullanıldı. Hot plate testi, farelerin analjezimetrenin 50±0.1ºC'deki metal yüzeyine bırakıldıkları andan itibaren, ayaklarını hızla çırptıkları veya yaladıkları süre saniye olarak ağrı eşiği değeri için kaydededilerek uygulandı.. Deneylerden önce hayvanlar 1 hafta süreyle hot plate'e alıştırıldı. Deney günü, analjezimetrede kontrol kayıtları alındıktan hemen sonra, intraperitoneal yolla farlı dozlardaki grelin uygulamaları yapıldı. Kontrol grubuna serum fizyolojik verildi. Bütün hayvanlara enjeksiyonlardan 30, 60, 90 ve 120 dakika sonra test uygulandı. Ağrı eşiği değerleri belirlendi ve Mann-Whitney U Test ve Wilkoxon Sign Ranks Test kullanılarak analiz edildi. Bulgular: Grelin kontrol grubuyla karşılaştırıldığında 0.3 pmol ve 1 pmol dozlarında ağrı eşiğini etkilemedi. 3 pmol dozda ise, 30. ve 60. dakikalarda ağrı eşiğinde belirgin azalmalar ortaya çıktı (p
Farelerde Ağri Eşiği Üzerine Grelinin Etkisi